Reducing Medication Waste While Improving Access to Sugammadex: A Quality Improvement Project in Medication Stewardship. Issue 7 (May 2020) - Pimentel, Marc Philip; Billings, Felicity; Sivashanker, Karthik; Sarin, Pankaj; Fields, Kara; Cotugno, Michael; Eappen, Sunil; Urman, Richard D.
Abstract : The relatively high cost of sugammadex compared to neostigmine limits its widespread use to reverse neuromuscular blockade, despite its faster onset and more complete clinical effect. While ensuring timely access to sugammadex is important in improving perioperative safety, it is also vital to control unnecessary spending. We describe a quality improvement initiative to reduce excess spending on sugammadex while improving access for anesthesia providers. Monthly spending on sugammadex decreased by 52% (70, 777 vs 33, 821), while medication access increased via automated medication dispensers in each operating room. Clinical usage decreased by one-third, with presumed increased adherence to dosing guidelines.